Petrology and Sedimentation of the Archean Quetico Metasediments in the Atikokan-Mine Centre Area, Northwestern Ontario - Pezzutto, Frank (1988)
A Thesis submitted to the faculty of the Graduate School of the University of Minnesota by Frank Pezzutto in partial fulfillment of the requirements for the degree of Master of Science, December 1988. Plate 1 referenced in the thesis is also attached to this record. The Quetico Subprovince in the Atikokan-Mine Centre region of Northwestern Ontario comprises an Archean gneiss-granite superbelt between the Wabigoon and the Wawa-Shebandowan Subprovinces to the north and south, respectively. A one-to two-kilometer wide marginal zone of low-grade metasedimentary rocks parallels the Quetico fault along the northern portion of the Quetico Subprovince in the study area. These metasediments are dominated by the resedimented facies association of greywacke, pebbly sandstone, mudstone and conglomerate. The metagreywackes are regularly bedded and graded and display sedimentary features typical of turbidite deposition. The stratigraphic nomenclature in the Rainy Lake area which was established at the beginning of the century by A.C. Lawson can still beapplied, although the stratigraphic relationships have been reversed. Poulsen and others (1980) have shown unequivocally that the Coutchiching Series (of which the Quetico Metasediments may be correlative) is not the oldest unit in the area because it overlies the Keewatin metavolcanic unit. However, the relationships between the Quetico metasediments, the Seine Series, and the Steep Rock Series still need to be resolved and and zircon geochronology should help in correlating these units. All rocks in the Quetico Subprovince have undergone at least greenschist facies metamorphism. The metasediments have been deformed, progressively metamorphosed southward and migmatized toward a central axis so that the original textures and most of the sedimentary features have been obliterated. The core of the Quetico Subprovince is made up of metasedimentary migmatite remnants, amphibolite, and granitic intrusives, many of anatectic origin. Bedding stikes east and dips are nearly vertical. ...